KETERLIBATAN PEMUDA DALAM PROSTITUSI ONLINE DI KOTA MANADO: TINJAUAN ETIKA TEOLOGIS DAN IMPLIKASINYA TERHADAP PEMBINAAN MORAL KRISTEN - Gracella Walukow (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2025)
Online prostitution is a behavior that has the potential to be destructive, where individuals can engage in interpersonal relationships without formal commitment or attachment to a marital relationship. Factors driving online prostitution include limited parental supervision, low education, economic pressure in the family, influence from media and technology, and interactions with peers. The impact of having an unhealthy relationship is the risk to physical and mental health, as well as disruption in social and family relationships. Christian religious education has an important role in dealing with youth who engage in online prostitution. Christian education teaches spiritual values, strong moral and ethical foundations, and can provide views regarding the dignity of humans as God's creation. Education with this model can also provide support to young people to stay away from online prostitution behavior and live a better life according to the teachings of Christianity. This research uses qualitative methods with a literature review approach to find out the role of religious education in preventing young people from engaging in online prostitution. So the aim of this article is to provide an insight into the factors driving young people to engage in online prostitution, its negative impacts and the role of Christian religious education in overcoming this problem.